PENINGKATAN KEAMANAN WEBSITE DARI SERANGAN CROSS SITE SCRIPTING (XSS) DENGAN METODE METACHARACTER DAN FORM VALIDATION - Fuad Bawazir Alatas, (2021)
Cross Site Scripting (XSS) is a common attack technique on a website. Because this technique is a fairly simple technique where the attacker only enters code injection which will later display or reflect data from the user. Because there are now many new websites, the use of the XSS (Cross Site Scripting) technique is increasing and there have been several cases that occurred throughout 2020. The solution offered in this research is to create security that can detect and prevent Cross Site Scripting (XSS) attacks. . This system can prevent XSS (Cross Site Scripting) attacks. This system can detect and prevent Cross Site Scripting (XSS) attacks by filtering the input. Metacharacter is used to replace input entered by the user in order to prevent XSS bugs caused by the payload originating from user input. Form validation is used to complete the deficiencies in the metacharacter to improve website security. After testing, it is found that combining the two filters can prevent the given payload, so it doesn't cause XSS bugs. The conclusion is that using metacharacters alone is not enough because there are still some unfiltered payloads so that when combined with form validation it can filter all the given payload tests.